A New Way of Looking at Risk and QD Compliance - Lon Santis; John Tatom; Michael Swisdak (International Society of Explosives Engineers, 2013)
The Institute of Makers of Explosives (IME) and A-P-T Research, Inc. (APT) have developed a quantitative risk assessment tool called IMESAFR (IME Safety Analysis for Risk) for managing risk from various activities undertaken in the commercial explosives industry. The first version was completed in 2006 and Version 2.0 of the software was completed in 2012, incorporating several major new features. The platform is now based on a Geographic Information System (GIS), providing a bird’s-eye-view to help visualize facility layouts and risk. Spatial data on potential explosion sites and exposed sites can now be automatically transferred from the images to ease users’ data input. Use of GIS data provides the ability to check facility compliance with quantity-distance (QD) standards such as the American Table of Distances (used by the Bureau of Alcohol, Tobacco, Firearms and Explosives, ATF), the NATO standard (used by Natural Resources Canada and other nations), or a user-defined table. Research conducted and knowledge gained over the last 10 years enabled changes in the algorithms and models that provide greater fidelity and reduce conservatism. Expert users can change global settings to more accurately match actual site conditions and the program runs using either Imperial (English) or SI (metric) units of measure. These changes and other new features are discussed and demonstrated.